TMIC-30. MICROGLIA/BRAIN MACROPHAGES PROMOTE GLIOMA GROWTH BY EXPRESSING GLYCOPROTEIN NMB - Yalcin, Fatih (Neuro Oncol, 2019)
BACKGROUND: Glioma-associated microglia and blood-derived macrophages (GAMs) promote tumor growth in experimental mouse glioma models. Using microarray and RNA sequencing, we have previously shown that GAMs upregulate the expression of Glycoprotein NMB/Osteoactivin (GPNMB) when compared to naïve microglia. GPNMB is a type 1 transmembrane glycoprotein expressed intracellularly under healthy conditions. Malignancies such as glioma induce a translocation into the plasma membrane where the extracellular domain can be cleaved and released. METHODS: We used qRT-PCR, immunocytochemistry, Western Blot and flow cytometry to determine the cellular localization of GPNMB expression in human and mouse glioblastoma. To test the impact of microenvironment-derived GPNMB on glioma growth, we inoculated GL261 and RCAS-PDGFb glioblastoma cells into organotypic brain slices obtained from wildtype and GPNMB-/- mice. In addition, we quantified glioma growth after injection of RCAS-PDGFb cells into wildtype and GPNMB-/- mice. The soluble extracellular domain of GPNMB was used to stimulate primary human glioblastoma and RCAS-PDGFb cells in vitro. SRB assays were performed to assess proliferation. RESULTS: Our data indicate that GAMs are the predominant source of GPNMB in both human and mouse glioblastoma and that the levels of expression in GAMs in the tumor microenvironment is higher than in naïve microglia. In the organotypic brain slice model we found that tumors were significantly smaller in slices derived from GPNMB-/- mice as compared to wildtype. The tumor growth in vivo was nearly completely blocked in the absence of GPNMB. Stimulation of glioma cells with the extracellular domain of GPNMB did not increase proliferation. CONCLUSION: Our results show that GPNMB is predominantly expressed in GAMs of human and murine samples. Loss of GPNMB impaired tumor growth ex vivo and glioblastoma progression in vivo. GPNMB seems to play a crucial role in the pro-tumorigenic activity of microglia and blood-derived macrophages in the tumor microenvironment.